DAMPAK ELECTRONIC BANKING TERHADAP KINERJA PERBANKAN INDONESIA - Margaretha, Farah (D-III Keuangan dan Perbankan, 2015)
The purpose of this research is to determine the effect of banking service to bank profitability.Â A dependend variable ratio in this research is internet banking. ItÂ is to test the effect of Return on Asset (ROA), Return on Equity (ROE), Operating Expenses towards Operating Income and Performance. Another ratio, that was used as a variable control, is asset. The method of data analysis is binary logistic regression. The object of the research is 68 banks in Indonesia. Those banks are divided into two groups, bank with and without internet banking. The result of this research shows that there is influence on internet banking service to effeciency profitability and different grouping. Finance Manager and Investor should pay attention the effect of ROA, ROE, BOPO and Asset.